2020
DOI: 10.1167/tvst.9.13.14
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Early Postnatal Biochemical Markers May Predict Development of Retinopathy of Prematurity

Abstract: Purpose Growth factors and inflammatory and angiogenetic proteins are involved in the development of retinopathy of prematurity (ROP). However, no early biochemical markers are in clinical use to predict ROP. By performing cluster analysis of multiple biomarkers, we aimed to determine patient groups with high and low risk for developing ROP. Methods In total, 202 protein markers in plasma were quantified by proximity extension assay from 35 extremely preterm infants on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…The specific proteins identified as most interesting by Lynch et al, such as superoxide dismutase (Mn), mitochondrial (MnSOD), proprotein convertase subtilisin/kexin type 9, and insulin-like growth factor-binding protein-7, have been examined, but not found significant in our analysis. Moreover, Markasz et al 21 have recently suggested the association of eight proteins, measured at postnatal age 2 days, with the later development of ROP. We have analyzed five of these proteins and cannot confirm a correlation to ROP or GA at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific proteins identified as most interesting by Lynch et al, such as superoxide dismutase (Mn), mitochondrial (MnSOD), proprotein convertase subtilisin/kexin type 9, and insulin-like growth factor-binding protein-7, have been examined, but not found significant in our analysis. Moreover, Markasz et al 21 have recently suggested the association of eight proteins, measured at postnatal age 2 days, with the later development of ROP. We have analyzed five of these proteins and cannot confirm a correlation to ROP or GA at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential of exploratory omics to increase the knowledge of preterm birth and ROP has been highlighted. 17 21 These studies display the power of extensive protein profiling as a tool for future precision medicine. Nonetheless, follow-up studies are required to confirm the targets for either therapeutic or diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster analysis showed that an early increase in the levels of Parkinson disease protein 7 (PARK7), vimentin, myeloperoxidase (MPO), CD69, and NF-κB essential modulator (NEMO) in plasma is related to a decrease in ROP risk. However, lower levels of tumor necrosis factor receptor superfamily member 4 (TNFRSF4) and higher levels of HER2 and galanin could predict the progression of ROP ( 118 ). In addition, a meta-analysis suggested that polymorphisms in the angiotensin-converting enzyme (ACE) I/D may be a genetic biomarker of an increased risk of ROP ( 119 ).…”
Section: Candidates Of Novel Potential Biomarkersmentioning
confidence: 99%